Organized Crime and the Objectives of the Islamic Penal System (Al-Qamar, 2023)
This article aims to analyze the application of the International Organized Crime Convention (UNTOC) to counter the global threat posed by organized crime. Organized crime is a complex and multifaceted phenomenon that poses a serious threat to international peace and security, generating an estimated $870 billion annually. The purpose of this study is to explore the effectiveness of the UNTOC in preventing and combating transnational organized crime, highlight the complexities in the UNTOC employment process, and explore the UNTOC's role in national and international efforts to combat organized crime. To assess and investigate the impact of the challenge posed by the UNTOC by new forms of transnational organized crime. The research questions are designed to examine UNTOC's specifications, its impact on national and international efforts to combat organized crime, implementation challenges, and the types of organized crime it seeks to deter and combat. The significance of this article is that it may provide legislators, law enforcement and other stakeholders with insights into combating organized crime and recommend ways to improve the effectiveness of the UNTOC.
Keywords: Organized Crime; Islamic; Penal System